Respuesta :

Answer:

Explanation:

3

Explanation:

The reaction expression is given as:

     Al(OH)₃  +   HNO₃   →    H₂O   +  Al(NO₃)₃  

To solve this problem, let us assign coefficient a,b,c and d to each specie;

          aAl(OH)₃  +   bHNO₃   →    cH₂O   +  dAl(NO₃)₃  

Conserving Al : a  = d

                  O:  3a + 3b  = c + 9d

                  H: 3a + b  = 2c

                  N: b  = 3d

let a = 1 , d  = 1, b  = 3 , c = 3

 Multiply through by 3;

a  = 1, b  = 3, c = 3 and d  = 1

  Al(OH)₃  +   3HNO₃   →    3H₂O   +  Al(NO₃)₃  

It’s c if this is wrong then I’m really sorry